Feasibility of sliding base isolation for rubble stone masonry buildings in the Himalayan Mountain range - Suzuki, Yusuke; Tada, Mayako; Enokida, Ryuta; Takagi, Jiro; Araki, Yoshikazu; Pareek, Sanjay; Lee, Sanghun; Ikago, Kohju; Guo, Jia; Shrestha, Kshitij C.; Fukuda, Iori; Masui, Takeshi (Frontiers in Built Environment, 2024)
This paper studied the feasibility of a sliding base isolation layer to be used in rubble stone masonry buildings in rural areas in the Himalayan Mountain range to provide robust protection to important building like schools against strong earthquakes. In this paper, we carried out on-site investigations, quasi-static tests, and shaking table tests focusing on constructability as well as isolation performance. From the results of the feasibility study, the combination of styrofoam, concrete slab, and grease was found to be the most feasible to be used as the upper element, the lower element, and the lubricant, respectively, in the sliding isolation layer. The key features of the present sliding base isolation layer are: 1) the use of the materials that exist in rural mountain areas or those that can be easily transported from the neighboring towns and cities and 2) ease of construction and minimal change from the current construction practice. From the shaking table tests, we identified the conditions, e.g., grease amount, grease type, normal stress at the interface, and roughness of concrete slab surface, to achieve dynamic friction coefficients ranging from 0.08 to 0.16, suitable for sliding base isolation.